Digestibility of Plants in Ruminal Fluids of Barren-Ground Caribou - Thomas, Donald C.; Kroeger, Peter (ARCTIC, 1981)
The comparative digestibilities of plants and their rates of digestion in vitro were assessed by fermentation with ruminal fluids obtained from barren-ground caribou (Rangifer tarandus groenlandicus) shot on their winter range in the southern Northwest Territories. There was a near-linear increase in the in vitro, dry-matter disappearance (IVDMD) with fermentation time (30-120 h) for all eight lichen species that we tested. In contrast, IVDMD was essentially maximal after 60 h fermentation for 10 of 11 non-lichen species. The green leaves of Carex rostrata and Equisetum variegatum were the only species with IVDMDs higher than 50% after a 60-63 h fermentation period. The two species of mosses and a liverwort were poorly digested (15-27%). The addition of 63 mg of urea to each tube markedly increased the digestibilities of both species of lichens tested, and that of Vaccinium vitis-idaea, but it lowered the IVDMD of Salix and Betula stems and the green and cured parts of Carex rostrata. The IVDMDs of four lichen species collected on the Canadian Arctic Islands were higher than those of eight terricolous species obtained from the mainland winter range of R. t. groenlandicus.Key words: Rangifer, caribou, in vitro, digestibility, forages, lichens, rates, Canada